2003
DOI: 10.1007/s00122-002-1091-1
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation and mapping of a family of LMW-gliadin genes: effects on dough properties and bread volume

Abstract: Analysis of a cDNA library from wheat cv Wyuna endosperm, indicated a significant size and sequence variation among seed-endosperm protein genes. In this study, a family of low-molecular-weight seed protein genes are analysed that are related to the gliadins and the low-molecular-weight glutenin subunits. Sequence analysis and comparison of these proteins showed that they are closely related to a 17-kDa protein from barley, epsilon hordein, which plays a role in beer foam stability in the brewing industry. Map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…For example, wheats giving flour of the strong type have been found to carry gliadin blocks 1A3 (or 1A4), 1B1, 1D1 (or 1D5), 6A3, 6B1, and 6D1 (or 6D2), which are markers of high gluten quality, frost hardness, and drought resistance. Functional studies of single gliadin by reduction and oxidation of flours containing proteins are useful in assessing the effect of a particular protein on functional properties of dough (Clarke et al, 2003). Redaelli et al (1997) have shown strong positive effects on dough extensibility by Gli-D1 (gliadins)/Glu-D3 (LMW-GS) alleles.…”
Section: Role Of Gliadins In Dough Rheologymentioning
confidence: 99%
“…For example, wheats giving flour of the strong type have been found to carry gliadin blocks 1A3 (or 1A4), 1B1, 1D1 (or 1D5), 6A3, 6B1, and 6D1 (or 6D2), which are markers of high gluten quality, frost hardness, and drought resistance. Functional studies of single gliadin by reduction and oxidation of flours containing proteins are useful in assessing the effect of a particular protein on functional properties of dough (Clarke et al, 2003). Redaelli et al (1997) have shown strong positive effects on dough extensibility by Gli-D1 (gliadins)/Glu-D3 (LMW-GS) alleles.…”
Section: Role Of Gliadins In Dough Rheologymentioning
confidence: 99%
“…Avenin-like a-type protein, with a molecular mass of about 18 kDa, contains 14 cysteine residues [22]. Based on the presence of highly conserved cysteine residues in the proteins from different species and its high sequence homology to ‘low-molecular weight gliadin’ monomer [25], [26], [27], it is presumable that cysteine residues of Avenin-like a protein mediate seven intra-chain disulfide bonds. The mature Avenin-like b-type proteins with a molecular mass of about 30 kDa contained 18 or 19 cysteine residues [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, farinins and ALPs share many structural similarities (Kasarda et al 2013). According to Kan et al (2006), ALPs are similar to oat avenins, and the oat avenins are similar to gliadins (Salcedo et al 1979;Anderson et al 2001;Clarke et al 2003). A comparison of gliadin, oat avenin, and farinins revealed that similarity between oat avenin and gliadin was higher than that between farinin and gliadin (Kasarda et al 2013).…”
Section: Introductionmentioning
confidence: 87%
“…ALP b-type genes were then reported from various Aegilops species that exhibited close evolutionary relationships with wheat (Chen et al 2008). The a-type ALPs were similar to LMW gliadins and were disengaged from the gluten polymer through S-S bonds (Clarke et al 2003;de Gregorio et al 2009). The b-type ALPs with 18/19 cysteine residues were of particular interest in determining the functional properties of gluten (Kan et al 2006), which was shown to enhance dough mixing properties when b-type ALPs were incorporated into gluten proteins (Chen et al 2010).…”
Section: Introductionmentioning
confidence: 96%